A comparison of linear and daily undulating periodized strength training programs - Caldwell, A. (2004)
The purpose of this study is to compare linear periodized (LP) and daily undulating (DUP) periodized strength training programs, and determine if either method of periodization elicits superior gains in 1 Repetitions maximums (1RM) for back squat (BS) and bench press (BP) (core exercises). Nineteen subjects (n=19) underwent a 6-week resistance-training (RT) program. Participants performed both BS and BP two day a week. The LP group linearly increased intensity while decreasing volume. While the DUP group daily changed intensity and volume. Total volume for both BS and BP were equal for both LP and DUP. Both BP and BS increased significantly from pre to post for both groups. However, there was no significant difference in pre-post strength measure in the LP compared to DUP.